Immagini di Istopatologia Atlante per le esercitazioni di Patologia Generale - Riccardo Caldini (Electronica, 2007)
This collection of images of Histopathology is the fruit of the authors' thirty years' experience in the performance of practical exercises in General Pathology. It is aimed at students attending lessons of General Pathology on the Degree Courses in Medical Surgery and Biological Sciences. It does not aspire either to be complete from the point of view of the various organic pathologies, or to replace direct and personal observation of the histological preparations through the microscope, but is rather intended as an aid to students preparing for the exam. It does not include the rudiments of cytology and microscopic anatomy, which it is assumed have already been mastered by those approaching General Histopathology, nor are histopathological phenomena systematically addressed, for which the reader is referred to textbooks on General Pathology. The 44 preparations presented here have been grouped in line with the main arguments of General Pathology: Cellular Degeneration, Inflammation, Neoplasia both benign and malign, and Vascular Pathology. They have been selected for their didactic significance and the simplicity and clarity of the lesions present, without taking into account the information to be derived from the clinical case history. The images of the preparations, in which the best possible quality of reproduction has been sought, are presented in progressive enlargements and are accompanied by brief descriptions comprising the explanations essential for identification of the characteristic aspects of the elementary lesion, as well as any eventual defects in the preparations themselves. Effectively, the objective of the work is to enable the student to exercise his understanding of the images. For this reason the casuistics included is as essential as possible, and the method of presentation utilised is designed to avoid mere visual memorisation, stimulating first analysis and then synthesis, and the development of individual logical skills so as to indicate whether aspects of cellular pathology, inflammation or neoplasia are present.